GIBELLINI, Rosino. A teologia do século XX. 3. ed. São Paulo: Edições Loyola, 2012 - Wischral Rodrigues, Marilze (Vox Scripturae - Revista Teológica Internacional, 2025)
GIBELLINI, Rosino. A teologia do século XX. 3. ed. São Paulo: Edições Loyola, 2012.